2017
DOI: 10.1016/j.molcel.2017.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute CLIP Defines a Deregulated miR-122-Bound Transcriptome that Correlates with Patient Survival in Human Liver Cancer

Abstract: Summary MicroRNA-122, an abundant and conserved liver-specific miRNA, regulates hepatic metabolism and functions as a tumor suppressor, yet systematic and direct biochemical elucidation of the miR-122 target network remains incomplete. To this end, we performed Argonaute crosslinking immunoprecipitation (Ago-CLIP) sequencing in miR-122 knockout and control mouse livers, as well as in matched human hepatocellular carcinoma (HCC) and benign liver tissue to identify miRNA target sites transcriptome-wide in two sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 70 publications
3
65
1
Order By: Relevance
“…Xing et al demonstrated in Huh7, HepG2, and QSG‐7701 cell lines that the expression of miR‐122 was inhibited by its promoter methylation, and that when miR‐122 promoter methylation was inhibited, it could restore its expression and subsequently induce apoptosis in these three HCC cell lines. Luna et al 33 found that miR‐122 was also significantly downregulated in HCC tissues and negatively correlated with a poor prognosis and metastasis. The upregulation of miR‐122 in HCC cell lines allows it to bind to the 3′‐untranslated region of the DLX4 gene directly and downregulate its expression, thereby inhibiting the proliferation and metastasis in HCC cells and inducing apoptosis by targeting AKT3 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Xing et al demonstrated in Huh7, HepG2, and QSG‐7701 cell lines that the expression of miR‐122 was inhibited by its promoter methylation, and that when miR‐122 promoter methylation was inhibited, it could restore its expression and subsequently induce apoptosis in these three HCC cell lines. Luna et al 33 found that miR‐122 was also significantly downregulated in HCC tissues and negatively correlated with a poor prognosis and metastasis. The upregulation of miR‐122 in HCC cell lines allows it to bind to the 3′‐untranslated region of the DLX4 gene directly and downregulate its expression, thereby inhibiting the proliferation and metastasis in HCC cells and inducing apoptosis by targeting AKT3 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we confirmed that increased BCL9 phosphorylation by aberrant CDK1 activation in cancer also contributes to mitotic Wnt signalling deregulation. In addition to phosphorylation, BCL9 gene expression has been shown to be highly enriched in many cancers, predominantly due to gene amplification (TCGA cbioportal, http://www.cbioportal.org/) and/or post‐transcriptional deregulation (Jia et al , ; Luna et al , ). In addition, the deregulation of mitotic progression regulators in cancer, such as spindle regulators (Chen et al , , ), might induce abnormal mitotic distribution and lead to aberrant activation of mitotic Wnt signalling, which eventually leads to cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, and most others in adipose tissue, rely on computational predictions and low-throughput validation to identify miRNA targets. Although high-throughput crosslinking techniques to map the miRNA targetome have been applied to liver, brain, heart and other tissues 11,12,13 , thus far, no comprehensive targetome has been described for adipose tissue.…”
Section: Figmentioning
confidence: 99%